EFEKTIVITAS TERAPI NAFAS DALAM TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Tiarnida Nababan (Jurnal Keperawatan Priority, 2022)
Deep breathing relaxation therapy can reduce blood pressure both systolic and diastolic pressure. Relaxation therapy diaphragm breathing techniques are very well done every day by people with high blood pressure to help relax blood vessel muscles so that the elasticity of the arteries that help lower blood pressure can be maintained. The purpose of this study is to investigate the effectiveness of breath therapy in reducing blood pressure in hypertensive patients at Royal Prima Hospital Medan. This is a quasi-expression research with cross sectional research design. The research populations were the average number of hypertensive patients at Royal Prima Hospital Medan in consisting of 73 people. The 22 samples were drawn using the accidental sampling technique. The results of the study on blood pressure variables before respiratory therapy showed that 15 people (68.2%) had normal blood pressure. Variable blood pressure after therapy breath in revealed that 15 people (68.2%) in normal condition were of 1 people (4.5%) and on weight was 6 people (27.3%). The results of the t test Test with a correlation of 0.001 or 0.1% with a significance value of 0.1% <5%, means that there is effects of deep breath therapy on decreasing blood pressure in patients with hypertension. The respondents are expected to apply breath therapy in well and regularly every day so that there is a drop in blood pressure to the normal level in hypertensive patients.